Immigrant self-employment: does intermarriage matter? - Dimitris Georgarakos; Konstantinos Tatsiramos (Institute for the Study of Labor (IZA), 2009)
This paper investigates the effect of a native spouse on the transitions into and out of entrepreneurship of male immigrants in the U.S. We find that those married to a native are less likely to start up a business compared to those married to an immigrant. This finding is robust when the endogeneity of being married to a native is taken into account. We also show that immigrants married to a native are significantly less likely to exit from entrepreneurship compared to their counterparts who are married to an immigrant. Our results point to an interesting asymmetric role of being intermarried in deciding to become an entrepreneur and for survival in entrepreneurship, which is consistent with a network effect. On the one hand, intermarriage reduces the chance of starting up a business possibly because better access to local networks can help transitions into other forms of employment (e.g. paid employment). On the other hand, superior access to local networks through marriage to a native spouse facilitates business survival.
urn:nbn:de:101:1-2009092280
Keywords: J12; J15; J61; 330; Business ownership; migration; native spouse; social networks; Migranten; Selbstständige; Ehe; Interkulturelle Beziehungen; Soziales Netzwerk; USA